(untitled) (Mustansiria Dental Journal, 2019)
Background: Radiographic discrimination of root end filling materials from surrounding tooth structure is clinically relevant for assessing the quality of retrograde treatment. The present study aimed at evaluating the radiopacity of Biodentine™ and Pro Root MTA as root end filling materials using a digital radiography technique. Materials and Methods: Specimens of BiodentineTM and Pro Root MTA test materials with 1mm thick and 10 mm internal diameter were prepared for digital radiographic analysis using an aluminum washer. The radiopacity of the Biodentine™ and Pro Root MTA was assessed using dental radiography equipment in combination with a phosphor plate digital system and a grey scale value aluminum step wedge with thicknesses varying from 1 mm to 10 mm in steps of 1 mm each. The degree of radiopacity of the test materials were radiographed and compared together with the aluminum step wedge on a computer screen using image J software. Radiopacity was expressed in mm of equivalent aluminum step wedge. The radiopacity values of Biodentine™ and Pro Root MTA were statistically analyzed using the one way analysis of variance (ANOVA) and post-hoc test (Bonferroni test), the level of significance was set at 0.05 (P<0.05). Results: The radiographic data showed that the degree of radiopacity of Pro root MTA is significantly higher than that of Biodentine™ (P<0.001). The current study reported that the ProRoot MTA showed requisite radiopacity around 5.86 mm when compared with aluminum step wedge steps, whereas the radiopacity of Biodentine™ determined around 2.46 mm of equivalent aluminum. Conclusion: The radiopacity of Pro Root MTA is clinically relevant that allows for clear distinction between the material and the surrounding tooth structure enabling it to be used as root end filling material. However, Biodentine showed reduced radiopacity that needs further improvement.